Photographic Documentation of Rare Enggano Palm Civet Paradoxurus hermaphroditus enganus (Carnivora: Viverridae) - Iqbal, Muhammad; Rais, Rendra Regen; Kuswanto, Adi; Pragustiandi, Guntur; Susatya, Agus (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2024)
Enggano Palm Civet Paradoxurus hermaphroditus enganus is a subspecies of Common Palm Civet Paradoxurus hermaphroditus that range limited in Enggano Island, Bengkulu Province, Southwest Sumatra. Since a specimen collection on 11 November 1904, the occurence P. hermaphroditus enganus has not ever been reported again. There are two recent observations of P. hermaphroditus enganus in 2011 and 2020. These observations are represent recent records of this rare endemic taxa after 107 years.